Exam ref 70-486 : developing ASP.NET MVC 4 web applications - Penberthy, William (Microsoft Press, 2013)
Prepare for Microsoft Exam 70-486--and help demonstrate your real-world mastery of developing ASP.NET MVC-based solutions. Designed for experienced developers ready to advance their status, Exam Ref focuses on the critical-thinking and decision-making acumen needed for success at the Microsoft Specialist level. Focus on the expertise measured by these objectives: Design the application architecture Design the user experience Develop the user experience Troubleshoot and debug web applications Design and implement security This Microsoft Exam Ref: Organizes its coverage by exam objectives. Features strategic, what-if scenarios to challenge you.